The dark side of intangibles? Organizational capital and corporate investment efficiency - Ahmed, Mohamed Shaker; King, Timothy (Emerald, 2025)
Purpose Organizational capital (OK) represents an important intangible productive firm asset, yet one subject to agency problems. This paper provides a first examination of how OK impacts corporate investment inefficiency using an unbalanced panel of listed US companies from 2009 to 2020. Design/methodology/approach We utilize fixed-effect regressions to explore the relationship between OK and investment efficiency. Additionally, we implement a battery of robustness tests of the main study findings based on a variety of panel data techniques, including firm fixed effects, alternative measures of investment efficiency, estimators, including Newey–West as well as additional steps to address endogeneity concerns using system-GMM, two-stage least-squares and entropy balancing analyses. Findings OK is associated with reduced investment efficiency (underinvestment and overinvestment). A one-standard deviation increase in OK to total assets is associated with a 4.42% decrease in investment efficiency. Based on average firm investment, this represents a $390.88 million decrease in investment. CEO gender and career concerns as well as R&D intensity, positively moderate this relationship, while CEOs’ age, power, tenure and connections as well as corporate governance and disclosure quality, negatively moderate it. The findings can be understood from the perspective of agency theory, whereby informational asymmetries surrounding OK make it challenging for firm outsiders to monitor and evaluate managerial investment choices. Originality/value We lack understanding as to how it impacts the efficiency of corporate investment. We contribute the first evidence in this regard by demonstrating that OK is associated with lower investment efficiency.
Keywords: Investment efficiency; Organizational capital; Capital allocation; Intangible assets; CEO characteristics; agency theory; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|